2011
DOI: 10.1589/jpts.23.519
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Subjective Risk Rating of Specific Tasks for Falls in Frail Elderly People

Abstract: Abstract.[Purpose] The purpose of this study was to examine the reliability and clinical usefulness of a subjective risk rating of specifi c tasks (SRRST) for assessing risks of falls in frail elderly people. The participants were 30 elderly individuals who utilized day-care services. [Subjects and Methods] Participants were investigated the SRRST, grip strength, one repetition maximum of leg-press machine (1RM), one-leg standing time (OLS), functional reach, timed up and go test (TUG), and 10 m-walking spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A single Level III study70 with small sample (n = 29) suggests that the Medical Outcome Short Form Health Survey (SF-36) Physical Activity Subscale score of less than 72.5 may be useful (PoTP = 54% if positive, PoTP = 20% if negative). Measures of caregiver concern71 and of overall health status41 were cited in single studies with small to moderate sample sizes. Neither demonstrated ability to identify fall risk.…”
Section: Resultsmentioning
confidence: 99%
“…A single Level III study70 with small sample (n = 29) suggests that the Medical Outcome Short Form Health Survey (SF-36) Physical Activity Subscale score of less than 72.5 may be useful (PoTP = 54% if positive, PoTP = 20% if negative). Measures of caregiver concern71 and of overall health status41 were cited in single studies with small to moderate sample sizes. Neither demonstrated ability to identify fall risk.…”
Section: Resultsmentioning
confidence: 99%
“…Our database searches identified a total of 4,310 unique records. After the two-stage screening and additional papers identified via the reference list search, a total of 55 papers are included in the review (Andresen et al, 2006;Ansai et al, 2016;Arai et al, 2020;Beauchet et al, 2010;Bergland and Wyller, 2004;Blain et al, 2021;Bongue et al, 2011;Briggs et al, 1989;Buatois et al, 2006;Buatois et al, 2010;Cho and Kamen, 1998;Choy et al, 2008;Choy et al, 2007;Crenshaw et al, 2020;de Rekeneire et al, 2003;Delbaere et al, 2010;Depasquale and Toscano, 2009;Ek et al, 2019a;Ek et al, 2019b;El-Sobkey, 2011;Eto and Miyauchi, 2018;Gerdhem et al, 2005;Hasegawa et al, 2019;Hashidate et al, 2011;Heitmann et al, 1989;Ikegami et al, 2019;Jalali et al, 2015;Kwan et al, 2011;Lim et al, 2016;Lin et al, 2004b;MacRae et al, 1992;Mahoney et al, 2019;Moreira et al, 2017;Muir et al, 2010;Mulasso et al, 2017;Nevitt et al, 1989;Niam and Wee, 1999;Park et al, 2020;Porto et al, 2020;Rossat et al, 2010;…”
Section: Resultsmentioning
confidence: 99%
“…Estimated heterogeneity in study outcomes in these meta-analyses was low for both cross-sectional (I 2 =14% (0,50%)) and longitudinal (I 2 =0% (0,60%)) analyses. Visual inspection of the funnel plot and Egger test (p=0.05) suggested that there may be minimal publication bias (see Appendix F); however, this was primarily driven by Cho and Kamen(1998;n= 16) and Hashidate et al(2011;n=30)(p=0.16 when removed), although there was no impact on the cross-sectional SMD when Cho and Kamen(1998) and Hashidate et al (2011) were removed from the meta-analysis (-0.28 (95% CI: -0.37,-0.19)).…”
Section: Mean Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The information of the SRRST and history of falls was obtained at the same time. Prior to the commencement of the study, three raters completed the SRRST twice at weekly intervals (n = 4 × 2 × 30), and test-retest and inter-rater (one physical therapist, one nurse, and two caregivers) reliability comparisons of total scores revealed intraclass correlation coefficients (ICCs) of 0.84 to 0.96 and 0.81, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%